Competence development in marine protected area professionals: a case study of the South African Marine Protected Area Management Training Course (SAMPATC) - Lewis, Sebastian Giulio (Rhodes University, Faculty of Education, Department of Education, 2012)
This study reviews a training programme on Marine Protected Area (MPA) management. It notes that although MPAs are well promulgated under legislation, reports have found that there are still key challenges facing the management of these areas. The research examines how the course was developed following the Lemm and Attwood (2003) report and designed to develop competences for effective MPA management. The aim is to identify how a MPA management training course produced competences apposite to the workplace settings of the participants. An interpretive case study method was used, in two phases. The first phase explored salient issues in MPA management in South Africa through analysis of the two key 'state of MPA management' reports and interviews with MPA professionals. The second was an analysis of the South African Marine Protected Area Management Training Course. This involved interviews with course designers, a review of the course materials, interviews with past course participants, and an analysis of course evaluations. Evidence emerged that supported the following findings: Challenges and problems facing MPA management still exist. Competence in key areas of MPA management was addressed in an effective work-integrated approach. Social learning was a key process in the development of these competences. The competences articulate well with the workplace of participants. Gaps exist between some of the management issues and the competences developed by the course, and some aspects of the course design are ineffective. From these findings it is concluded that: The course took up the majority of issues in MPA management through the development of key competences. The course design facilitated the development of these competences. The competences developed through the course are relevant to the workplace of MPA professionals. The research found that the course adequately addresses issues in MPA management through the development of competences. Some recommendations for improvements are made.
Keywords: Core competencies; Employees -- Training of; Marine ecosystem management